«Make love, not war». Communitarian life experiences as laboratories of peace education in Italy - Gianfranco BANDINI (Ediciones Universidad de Salamanca, 2017)
The 1960s and 70s in Italy marked a moment of great discontinuity, change and generational conflict. In these years of student protests, original and alternative lifestyles came to light: young people wanted to personally engage in a concrete and real experience of peace, brotherhood and sharing property (and in some cases also personal affections), breaking out of the roles imposed by the bourgeois family. The pacifism of these first Italian «communes» eclectically mixed the American dream with Eastern spirituality; rebellion and drug use with Marxist ideologies stemming from various sources. The result was a substantially minority (but not fleeting) movement which had ties both with its nineteenth-century predecessors (of both religious and socialist origin) and with some subsequent interesting twentieth-century experiences, up to the present day. The communitarian ideal took shape in some experiences which became increasingly interconnected, and so went on to form an international movement. While, in terms of numbers, the people choosing to live in communitarian form (also in the recent eco-villages or cohousing) were few, their way of thinking started to be shared by increasingly broad swathes of the population, with evident effects on lifestyles (such as buying organic foods) and forms of education. In particular, think of their refusal to do military service, openness towards Eastern spirituality, vegetarianism, their ecological vision, fight against vivisection and for animal rights, and so-called critical consumption. In Italy, the latter aspect developed above all thanks to Francesco Gesualdi, a pupil of Don Milani who pursued the ideal of a peace that was never detached from justice: with his activity and writings he made consumers responsible, engaging them in a form of non-violent protest against the waste and violence of the economic world. Unfortunately, we must not forget that not all the promises of brotherhood and communitarian joy were fulfilled. Some communities, in the secrecy of their isolated world, practised forms of coercion and violence, even against children. These cases, some of which have been subject to criminal investigations by the judiciary, show how the danger is not to be found in the drugs or the feared sexual promiscuity of the outset, but in the very character itself of small communities, by definition different from the rest of the social body and purposefully, physically separate. Such that, paradoxically, in these communities' history, violence and peace interweave.